The intersection of local wisdom and digital innovation in performing arts - Hafizhah Insani Midyanti; Yudi Sukmayadi (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2021)
Utilizing technology in cultural and locally-influenced performing arts alters the conventional understanding of aesthetic experiences in live performances. It includes redefining the dynamics between performers and audiences, the impact of sound and ambience, dance and visual elements, collaboration among artists, cultural aspects, environmental factors, and temporal considerations. Furthermore, digital technology has emerged as a novel means in the performing arts realm, streamlining the artistic creation process. Currently, the field of performing arts is significantly influencing the swift advancement of digital technology. This research methodology employs a qualitative approach by utilizing internet literature and conducting literature studies. The outcome of this study indicates that digital technology facilitates the comprehension of artistic performances rooted in local culture and knowledge by both the general audience and the current youth population. The intersection between technology, local wisdom, and performing arts is evident due to the transferability of local wisdom throughout generations and the continuous development of technology over time. Digital technology has broadened the scope of creativity, pushed the limits of artistic expression, and safeguarded traditional local knowledge.